Acting on delusions: the role of negative affect in the pathway towards serious violence. Issue 5 (3rd September 2018) - Ullrich, Simone; Keers, Robert; Shaw, Jenny; Doyle, Michael; Coid, Jeremy W.
ABSTRACT: Acting violently on delusions is a significant clinical problem. Recent research has identified state anger as key component in the pathway from persecutory/threat delusions to serious violence. To determine the magnitude of the effect of delusional anger and to investigate a dose-response relationship we carried out a prospective follow-up study of forensic in-patients discharged into the community. Men and women ( n = 409) were assessed before/after discharge at 6 and 12 months (Positive and Negative Syndrome Scale, MacArthur Community Violence Interview). No association was found with a content un-specific measure of delusions, thought disorder, hallucinations, grandiosity and violence. Suspiciousness/persecution was significantly associated with both violence and anger. Anger was also associated with violence. Mediation analyses suggested that 84% of the association between suspiciousness/persecution and violence was explained by anger. Key target of interventions should primarily be the anger; treatment of delusional beliefs plays a secondary role in the management of risk.